The history of Angolan education 1930-1980: the convergence of colonialism, religion, and decree - Bondo, Pedro Felisberto Miguel (Kansas State University, 2015)
Angola began as a Portuguese colony in 1655. All of its social structures and associated sectors, including education, were influenced drastically by this initial Portuguese colonization. This research concerns Angolan education from the years 1930-1980. Two distinct periods are addressed: the colonial period from 1930 to 1975 and the post-colonial period from 1975 to 1980. In both periods, education was provided by the state and by different religious denominations. However, the main argument for this research is that a general comprehensive history of education in Angola has not yet been written, in part due to the character of its colonization and decades of social instability related to its War of Independence, 1961-1975, and the Civil War, 1975-2002. In Angola under the Salazar and Caetano regime, provision for education was made according to the Colonial Act of 1930, the new state, and the rule of the Roman Catholic and Protestant missions. Despite the concourse of these institutions staging events that influenced education and the whole culture, few Angolans were allowed to attend school and participate as citizens in society. The post-colonial period from 1975 to 1980 is characterized by the foundation of a socialist educational system. Most of the existing documents concerning Angolan education were written by the colonizers or by those who regard history from a colonial perspective. Therefore the history of education in Angola, as the convergence of colonialism, religion, and decree, needs to be rewritten.
Keywords: History of education; Postcolonial theory; Religion; Angola; Colonialism; Teacher education